Management of Antithrombotic Therapy in Left Ventricular Thrombus: A Position Paper of the Italian Society of Hemostasis and Thrombosis (SISET) - Valeriani, Emanuele; Pannunzio, Arianna; Menichelli, Danilo; Prisco, Domenico; Ageno, Walter; Pastori, Daniele; Pignatelli, Pasquale (Thrombosis and Haemostasis, 2025)
Left ventricular thrombus (LVT) represents a potential life-threatening condition burdened by a significant risk of systemic embolism. Despite the relevance of the disease, there are scanty data on antithrombotic management of LVT mostly deriving from small observational studies and few randomized controlled trials. It has been reported that anticoagulant therapy reduces the rate of thrombus formation, allows thrombus resolution in most cases, and limits the risk of embolic complications. Several issues, however, still remain unresolved and clinicians caring for these patients have to decide on the need and on the regimen of antithrombotic therapy based on their expertise and data from different clinical scenario. This position paper of the Italian Society of Hemostasis and Thrombosis (SISET) aims to provide practical advice and guidance in the form of text, tables, and figures for clinicians dealing with LVT. Relevant clinical questions related to LVT have been identified concerning the identification of patients at risk; the role of anticoagulant prophylaxis on LVT development; the type, dose, and duration of anticoagulant therapy; and the management of patients receiving concomitant antiplatelet therapy. A systematic search has been performed to identify available evidence on the topic that has been carefully and critically reviewed by the national expert authors to support the suggestions and recommendations.
Keywords: acenocoumarol; anticoagulants; heparin; venous thromboembolism; warfarin